Regulated necrosis-related molecule mRNA expression in humans and mice and in murine acute tissue injury and systemic autoimmunity leading to progressive organ damage, and progressive fibrosis. Issue 6 (9th December 2016) - Honarpisheh, Mohsen; Desai, Jyaysi; Marschner, Julian A.; Weidenbusch, Marc; Lech, Maciej; Vielhauer, Volker; Anders, Hans-Joachim; Mulay, Shrikant R.
Abstract : The species-specific, as well as organ-specific expression of regulated necrosis (RN)-related molecules, is not known. We determined the expression levels of tumour necrosis factor receptor-1 (TNFR1), receptor activated protein kinase (RIPK)1, RIPK3, mixed lineage kinase domain-like (MLKL), CASP8, Fas-associated protein with death domain (FADD), cellular inhibitor of apoptosis protein (CIAP)1, CIAP2, glutathione peroxidase-4 (GPX4), cyclophilin D (CYPD), CASP1, NLRP3 and poly(ADP-ribose) polymerase-1 (PARP1) in human and mouse solid organs. We observed significant differences in expression of these molecules between human and mice. In addition, we characterized their expression profiles in acute as well as persistent tissue injury and chronic tissue remodelling using acute and chronic kidney injury models. We observed that the degree and pattern of induction of RN-related molecules were highly dependent on the trigger and disease pathogenesis. Furthermore, we studied their expression patterns in mice with lupus-like systemic autoimmunity, which revealed that the expression of MLKL, GPX4 and PARP1 significantly increased in the spleen along disease progression and CASP1, RIPK1, RIPK3 and CYPD were higher at the earlier stages but were significantly decreased in the later stages. In contrast, in the kidney, the expression of genes involved in pyroptosis, e.g. NLRP3 and CASP1 were significantly increased and TNFR1, RIPK1, RIPK3, CIAP1/2 and GPX4 were significantly decreased along the progression of lupus nephritis (LN). Thus, the organ- and species-specific expression of RN-related molecules should be considered during designing experiments, interpreting the results as well as extrapolating the conclusions from one species or organ to another species or organ respectively.